2022
DOI: 10.3390/ijerph191610436
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Public Health among People with Disabilities: Research Gaps and Recommendations

Abstract: Physical activity has become an integral component of public health systems modeling the public health core functions of assessment, policy development, and assurance. However, people with disabilities have often not been included in public health efforts to assess, develop policies, or evaluate the impact of physical activity interventions to promote health and prevent disease among people with disabilities. Addressing the core function of assessment, current physical activity epidemiology, and surveillance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…The results were analyzed into various research gap categories that is conceptual, contextual and methodological gaps Conceptual Gap: Martinez (2017) explored the intersectionality of gender, sexuality, and disability among LGBTQ+ individuals accessing healthcare. While this study provides valuable insights into the compounded barriers faced by LGBTQ+ individuals with disabilities, there is a conceptual gap in understanding the specific healthcare needs and experiences of LGBTQ+ individuals from diverse cultural backgrounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were analyzed into various research gap categories that is conceptual, contextual and methodological gaps Conceptual Gap: Martinez (2017) explored the intersectionality of gender, sexuality, and disability among LGBTQ+ individuals accessing healthcare. While this study provides valuable insights into the compounded barriers faced by LGBTQ+ individuals with disabilities, there is a conceptual gap in understanding the specific healthcare needs and experiences of LGBTQ+ individuals from diverse cultural backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…By highlighting the nuanced interplay of intersecting identities, the study underscored the importance of implementing tailored interventions and support systems, such as culturally responsive pedagogy and equitable resource allocation, to address the unique needs of this population and promote educational equity. Martinez (2017) explored the intersectionality of gender, sexuality, and disability among LGBTQ+ individuals in accessing healthcare services. Their research shed light on the compounded barriers faced by LGBTQ+ individuals with disabilities, including discrimination, lack of provider knowledge, and physical accessibility issues within healthcare settings.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Heath and Levine [40] reported that 20.6-50.0% of adults with disabilities met the WHO guidelines for PA in high-income countries, compared to 23.4-50.0% in low-and middle-income countries. The reported prevalence of PA among individuals without disabilities in high-and low-income nations was estimated to be 50% to 80% [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This supports the notion that our integrated approach could have multifaceted benefits, addressing both musculoskeletal and cardiovascular aspects. Moreover, high-intensity exercise has been found to reduce pain, disability rate, and psychological stress in PML patients [90,166,167].…”
Section: Discussionmentioning
confidence: 99%